Don’t Waste My Time; Exploring the Reflective Journaling Requirement in the Student Teaching Experience - Amy Spiker (Networks: An Online Journal for Teacher Research, 2014)
For many years reflective journaling has been a required component of the student teaching experience at my university. The students I supervise are required to reflect upon their teaching experience in writing. Journaling has evolved over the past few years from a traditional paper and pencil journal to journals that allow more flexibility and choice. Students can now record their journal on a word processor or write a dialogue journal with their mentor teacher.